Análise posicional de jogadores brasileiros de futebol utilizando dados GPS - Gasparini, Randal (2018)
The professional soccer is always changing and is constantly searching tools and data to help the decision-making, providing tatics and techniques to the team. In Brazil, this sport goes to same way and the investiments are considerables. The One Sports is a company that capture GPS data from professional soccer players of some brazilian teams. This set of data has a lot of features and the One Sports asked if was possible to predict the ideal position of a player. Then, was firmed a cooperation between a academic study and a comercial company. This work find to understand a propose methods and techniques to predict the ideal position of soccer player, using machine learning algorithms. The database has more of one million of tuples. It was submited to pre-processing step, what is fundamental, because generated new features, removed incomplete and noisy data, generated new balaced dataset and delete outliers, preparing the data to execution of the algorithms k-NN, decision trees, logistic regression, SVM and neural networks. With the purpose to understand the performance and accuracy, some scenarios was tested. There was poor results when executed multi-class problems. The best results come from binary problems. The models k-NN and SVM, specifically to this study, had the best accuracy. It is important to note that SVM spent more than six hours to finish your execution, and k-NN used less than one and half minute to end.